Experience with intrauterine insemination - Vargas, Luis (2015)
We found satisfactory results with homologous intrauterine insemination at Arzobispo Loayza Nationa Hospital Fertility Service. Ovulation induction wit clomiphene citrate apparently contributes to improve success. We could not obtain good results wit astenozoopermia with this technique, but heterologous intrauterine insemination used in azoospermia had better success.